PENGARUH PENDEKATAN SAINS TEKNOLOGI MASYARAKAT TERHADAP HASIL BELAJAR IPA DI SD - Alifa Hasana Pratiwi; Kartono Kartono; Suhardi Marli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this research was how to influence science technology societyapproach towards learning outcomes of students in learning the nature of science that was implemented in the class IV elementary school North of Pontianak 33 Country. In this study, researchers used a Quasi experimental design design design with the shape Nonequvalent control group design. The population in this research was the whole grade IV elementary school the country 33 North of Pontianak, while samples obtained through consideration of the ability of the students in the form of an odd year semester rapot values the lessons 2017/2018. Data collection techniques used ware measurement techniques and data collection tools used in the form of a written objective-shaped test. Based on the calculation of the average results it obtainedstudying post-test control class 71.38 and average post test experimental class of 75.59 so get thitung post data-test of 2.553 with ttabel to an extent α = 5% and dk = 65 of 1.670, because thitung (2.553) > ttabel (1.670) then the Ha received. So, there  was a significant influence on the use of science technology society approach towards learning outcomes students natural science grade IV elementary school North of Pontianak 33 Country. The calculation of effect size (ES) acquired for 0.44 (criteria are). This means the use of a science technology society's approach to exert influence.Key words : The influence of Science Technology Society, approach to Student Learning Outcomes in learning Science